An analytical study of the role of indicators of tax disputes in evaluating the performance of tax control in accounting- case study of Algeria (2016-2020 - Laggoune, rachid; bousmaha, mohamed (Journal of Research in Finance and Accounting, 2022)
This study aimed to highlight the performance of tax control in accounting through tax litigation indicators, then to know the extent of the commitment of accounting auditor in the application of tax codes to avoid tax litigation. By returning to the main issue of: What is the performance of tax audit in accounting through indicators of administrative tax litigation? Where this study has dealt with the theoretical framework of tax audit, in addition to the theoretical framework of tax litigation by applying to the case of Algeria on the basis of reports prepared by the General Directorate of Taxes from 2016 to 2020, and the he study concludes that the indicators of tax litigation are important to know the performance of tax control in accounting.